Review on circular-linear regression models - Hanin Hazwani, Mohammad; Siti Zanariah, Satari; Wan Nur Syahidah, Wan Yusoff (IOP Publishing Ltd, 2021)
Classical linear statistics method is no longer appropriate when handling circular data since the data is influenced by direction or angle. Considering the possibility of circular data appeared as dependent variable, it has resulted in the remodeling of classic linear regression model into circular-linear regression model over the past few decades. It is important to acknowledge these circular data characteristics as it can affect the descriptive and inference of statistical analysis. With the growing body of literature regarding this issue, this paper will review on circular-linear regression model by highlighting and exploring their benefits and limitations.